Short communicationFunctional assessment of a left coronary-pulmonary artery fistula by coronary flow reserve - Sasi, Viktor; Nemes, Attila; Forster, Tamás; Ungi, Imre (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
We report a 71-year-old man who presented with atypical chest pain. Coronary angiography did not reveal left main or proximal left anterior descending coronary artery stenosis, but a fistulous communication with a stronger tube-like fistula was present originating from the proximal left anterior descending coronary artery and emptying into the main pulmonary artery. Fractional flow reserve and coronary flow reserve measurements were performed to gain more data on the potential functional aspects of this fistula. With the present case, the importance of functional evaluation of these fistulas is demonstrated.